Mindfulness in student life: A phenomenological study of self-awareness, emotional resilience, and identity development - Ahmad Fadil; Amelia Zoraya; Lilik Sriyanti (Universitas Mercu Buana Yogyakarta, 2026)
This phenomenological study explored the meaning of mindfulness in the daily lives of university students. In-depth interviews were conducted with three active students at UIN Salatiga to understand how mindfulness is perceived and experienced in the academic, emotional, and social contexts. Using descriptive-interpretative analysis based on Giorgi’s “whole–part–whole” method, five essential themes were identified: present-moment awareness, emotional self-regulation, self-acceptance, adaptive coping, and reflective growth. The findings reveal that mindfulness is not merely a stress management technique but an existential and developmental process that simultaneously strengthens self-awareness, emotional resilience, and identity development as an integrated outcome. Participants demonstrated the ability to stay grounded in the present moment, consciously regulate their emotions, and make decisions aligned with personal and social values reflecting the dynamic formation of their identity. This study underscores the importance of developing mindfulness-based psychoeducational programs within higher education to holistically support students’ mental well-being, self-understanding, and personal growth, including the process of identity development.